Preparation, Characterization And Photocatalytic Applications Of Immobilized Polyaniline Coated Titania Composite For The Removal Of Dye And Diuron From Aqueous Solution - Abdul Razak, Mohd Fairul Sharin (2014)

(untitled)
P-25TiO2/PANI/ENR/PVC composite photocatalyst has been successfully fabricated and immobilized onto glass plates via a dip coating method. Dip coating dispersion was prepared by simple mixing of soluble polyaniline (PANI) with P-25TiO2 powder in the dichloromethane-toluene solvent containing epoxidized natural rubber (ENR) and polyvinlycholoride (PVC) which function as binding agents. Fotomangkin P-25TiO2/PANI/ENR/PVC telah berjaya dihasilkan dan dipegunkan pada plat kaca melalui kaedah penyaduran celup. Ampaian penyaduran celup telah disediakan oleh pencampuran ringkas PANI terlarut dengan serbuk P-25TiO2 dalam pelarut diklorometana-toluena yang mengandungi getah asli terepoksi (ENR) dan polyvinilklorida (PVC) yang berfungsi sebagai ejen pengikat.